(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The mechanical characterization of soft biological tissues remains a significant challenge in biomedical engineering due to ethical and practical constraints in obtaining living tissue specimens. This study presents an experimental and computational framework employing commercial silicone elastomers as biofidelic analogues for soft human tissues. Uniaxial tensile tests were performed using a custom low-cost setup; Young’s moduli ranging from 0.06 to 0.47 MPa were measured across strains of 0.23–2.36, values that align closely with published mechanical data for human adipose, breast, and liver tissues. Loading–unloading cycles were conducted to characterize mechanical hysteresis and viscoelastic energy dissipation. Additionally, a novel web application, BioMech Analyzer, was developed to automate stress–strain computation, hysteresis loop visualization, and real-time comparison of experimental moduli against a curated human tissue database via a "Tissue Matching Score" index. Results confirm that commercial silicone can serve as an accessible, tunable phantom material for biophysical modeling, with direct implications for medical device testing, surgical training, and educational biophysics laboratories.